2018
DOI: 10.1177/1534735418786801
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefits of Acupuncture for the Reduction of Hormone Therapy–Related Side Effects in Breast Cancer Patients: A Systematic Review

Abstract: Importance. Acupuncture can help reduce unpleasant side effects associated with endocrine therapy for breast cancer. Nevertheless, comprehensive evaluation of current evidence from randomized controlled trials(RCTs) is lacking. Objective. To estimate the efficacy of acupuncture for the reduction of hormone therapy-related side effects in breast cancer patients. Evidence review. RCTs of acupuncture in breast cancer patients that examined reductions in hormone therapy–related side effects were retrieved from Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 47 publications
1
26
0
1
Order By: Relevance
“…A heterogeneous response rate of acupuncture for hot flashes has been reported by many studies 12,19,20 and observed by our acupuncture practitioners. This should not be surprising considering well-known variations in disease response to many conventional treatments.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…A heterogeneous response rate of acupuncture for hot flashes has been reported by many studies 12,19,20 and observed by our acupuncture practitioners. This should not be surprising considering well-known variations in disease response to many conventional treatments.…”
Section: Introductionsupporting
confidence: 58%
“…Another large randomized clinical trial found that compared with enhanced usual care alone, the addition of acupuncture was superior in reducing hot flashes and improving quality of life among breast cancer patients. 18 A heterogeneous response rate of acupuncture for hot flashes has been reported by many studies 12,19,20 and observed by our acupuncture practitioners. This should not be surprising considering well-known variations in disease response to many conventional treatments.…”
Section: Introductionmentioning
confidence: 68%
“…Acupuncture use among breast cancer patients in the US is currently as high as 16% to 63% [606]. At the current time breast cancer related lymphedema is incurable but well manageable by a number of physical therapy modalities, especially complete decongestive therapy (CDT) [607]. Obesity is a factor that deteriorates the CDT efficacy.…”
Section: Alternative Therapies and Mind-body Interventionsmentioning
confidence: 99%
“…Acupuncture, which is one of the important elements of traditional Chinese medicine, is a scientific treatment that enables the body to regain its balance as a result of stimulation of special points in the body with needles. Acupuncture is effective in reducing chronic pain in cancer patients by exerting secretion of enkephalins and increasing serotonin levels from endogenous opioids known to have an effect on regulating mental and psychological state [33][34][35]. In studies with cancer patients with pain, acupuncture has been found to be a complementary, self-medicating, nonmedication treatment that reduces cancer-related symptoms (pain, digestive problems, neuropathy), and is selfmedicating [36][37][38][39].…”
Section: (Ii) Acupuncturementioning
confidence: 99%